Endogenous CD5L controls the metabolic and inflammatory state of human macrophages - Rasheed, Kashif; Moharrami, Neda Nejati; Tande, Erlend Bjørkøy; Espevik, Terje; Yurchenko, Maria; Boyartchuk, Victor (Frontiers in Immunology, 2026)
IntroductionCD5L is a scavenger receptor-like molecule that mediates diverse physiologic processes, including cell survival, atherogenesis, inflammation, and lipid metabolism. Even though CD5L is an abundant circulatory protein, it has recently become apparent that its expression can alter inflammatory signaling in a cell-autonomous fashion. To date, the effect of endogenous CD5L expression in human macrophages remains largely unexplored. Our work addressed this question by analyzing the impact of CD5L gene disruption on the inflammatory state of the THP-1 human monocytic cell line.ResultsIn macrophage-like CD5L-knockout cells, we observed a dramatic decrease in the basal expression of a subset of NF-κB-regulated genes when compared to control cell lines. These differences persisted after stimulation with lipopolysaccharide (LPS), even though the magnitude of induction was similar in both mutant and control cells. Consistent with the lipid remodeling function attributed to CD5L, we found significant changes in the makeup of the intracellular lipid pool. However, we did not detect significant changes in the activity of fatty acid synthase, which has been suggested to mediate CD5L lipidome remodeling function. Furthermore, we explored how CD5L function impacts undifferentiated monocytes. We found that in undifferentiated, unstimulated monocytes deleted for CD5L, several dysregulated transcripts code for genes involved in cell-to-cell interactions and in the progression of atherosclerosis. Most importantly, we found that CD5L deletion upregulates the expression of CD52, a novel anti-inflammatory switch.DiscussionOverall, our findings further support the multifunctional nature of CD5L and, for the first time, suggest its involvement in monocyte localization to sites of future lesions.